Student metacognition in online learning using website hyperlink facilities on Microsoft Team’s platform - Puguh Karyanto; Aris Nur Rohman (University of Muhammadiyah Malang, 2024)
Without the ability to analyze their own learning (metacognition), students can find it difficult to manage their educational journey. The good news is, future learning environments on online platforms offer innovative ways to develop these skills, even for those who are digital natives. This study aims to ascertain the effectiveness of online learning by using a website hyperlink-based teaching and learning scenario, especially using the Microsoft Teams platform towards students’ metacognition during online learning. Both metacognition knowledge and awareness (regulation), representing the metacognition, were checked. Coordination systems in learning biology were the chosen topics to be taught in quasi-experimental research using a pretest-posttest nonequivalent control group design. Two classes were selected purposely based on the normality and homogeneity test to have the controlled and experimental classes. We examined the metacognitive knowledge and awareness using tests and questionnaires. We checked the effectiveness of the web hyperlink-based media on students’ metacognition knowledge and awareness using MANOVA Regression analysis and N-Gain scores. Our developed web hyperlink-based media has significantly enhanced students’ cognitive knowledge and awareness.